Humanism and Aesthetics in the Light of Udo Etuk’s Perception - Otto, Dennis; Udoh, Moses (GNOSI: An Interdisciplinary Journal of Human Theory and Praxis, 2024)
The meaning of life or the world is as individuals perceive it. While some may claim that life is beautiful and pleasant, others may claim that it is ugly and unpleasant. And either of the perceptions is valid, insofar as it is an expression of authentic personal experience of the individuals expressing it. The perception emanates from some form of doctrine or culture that the individuals cultivate and commit themselves as they advance through life. This is the reason for individuals’ disparity of perceptions even on identical ideas or objects. Accordingly, while some people with religious orientation of life may claim that an idea or object is beautiful because God made it so, others with humanist conviction may claim of the same idea or object that it is beautiful because man made it so. This disparity in perception and meaning-making of life, particularly along religious and humanist lines, has been a subject of huge and extensive debate right from antiquity till the present. And this essay is an exercise in the debate. It specifically discusses aesthetic perception of life along humanist convictions. Among numerous types and approaches to humanism available, the essay adapts Udo Etuk’s New Humanism for its conclusion.